Efficacy analysis of a novel sternoclavicular hook plate for treatment of unstable sternoclavicular joint dislocation or fracture. (16th February 2017) - Zhang, Chuanyi; Lin, Lie; Liang, Junbo; Wang, Bin; Chen, Guofu; Chen, Haixiao
Purpose: Sternoclavicular joint is an amphiarthrodial joint formed by the clavicle and sternal manubrium. This joint becomes chronically unstable in case of a medial clavicle dislocation or fracture, and improper treatment could cause malformation and pain. We aimed to determine the efficacy of a novel sternoclavicular hook plate for treatment of unstable sternoclavicular joint dislocation or fracture. Methods: Between June 2011 and December 2013, the sternoclavicular hook plate was used to surgically treat 32 adult patients with unstable sternoclavicular joint dislocation or fracture. Of these, 12 and 5 patients suffered from anterior and posterior dislocation of the sternoclavicular joint, respectively, 10 had medial clavicle fracture, and 5 had fracture dislocation. For anterior fracture dislocation, the standard sternoclavicular hook plate was used, while for the posterior dislocation, screws were added at the distal end of the hook plate, anterior to the sternal manubrium, to prevent postoperative redislocation. Results: No intraoperative complications were observed during the procedure. Postoperative X-ray and computed tomography revealed normal anatomical positions of sternoclavicular joints and excellent positions of internal fixation. About 3–6 months after surgery, all patients achieved primary healing without redislocation of the sternoclavicular joint along with satisfactory restoration of anatomical structures of the medial clavicle; nine patients had swelling but no pain around the sternoclavicular joints. Internal fixation was removed in 29 patients 6–12 months postoperatively and no sequelae were observed. Conclusion: This novel sternoclavicular hook plate demonstrated excellent efficacy and could provide a reliable therapeutic approach for this kind of trauma.